Penerapan Economic Order Quantity (EOQ) dalam Menganalisis Persediaan Bahan Baku Agregat Halus Produksi Buis Beton Di UD. KI - Malisi, Sibro; Sundari, Susanti; Suwarni, Putri Endah (Fakultas Teknik Universitas Tulang Bawang, 2024)
UD. KI is an industry that produces Buis Benton type precast concrete. The materials that make up concrete blocks are cement, water, and coarse and fine aggregates. The supply of coarse aggregate is obtained from Gunung Sugih river sand, where availability is greatly influenced by flood conditions during the rainy season where there is a slight shortage which causes an increase in order prices. If the company wants to take steps to secure stock of sand raw materials to anticipate increases in order costs and ensure production continuity, this will disrupt the balance of production capital costs and the availability of storage space. Therefore, it is necessary to measure raw material inventories so that companies can take safety measures to anticipate increases in order costs and ensure production continuity. Analysis of the supply of coarse aggregate raw materials in concrete buis production at UD. KI uses the Economic Order Quantity (EOQ) method. By implementing the EOQ method, ordering value can be saved by 214.04 tonnes in 2021 and 173.28 tonnes in 2022, and there has been a significant reduction in the order frequency level from 12 times to 2 times per year, with a safety stock of 61.74 tons. Keywords: Coarse aggregate, Buis concrete, EOQ, Safety stock